violência AUTORREFERIDA EM RIO BRANCO, ACRE: INQUÉRITO POPULACIONAL - Lago, Rozilaine Redi; Ferreira, Terezinha de Freitas; Koifman, Rosalina Jorge; Muniz, Pascoal Torres (Revista Baiana de Enfermagem‏, 2014)